Implications of Parenting Patterns on the Emotional Development of Student in Islamic Boarding Schools - Irmayani, Ade; Pitaloka, Ayu; Aguslim, Aguslim; Lubis, Lahmuddin (Continuous Education: Journal of Science and Research, 2025)
This study aims to describe the implications of parenting styles on the emotional development of students in Islamic boarding schools. This study uses qualitative research with a library approach, namely a series of studies related to library data collection methods, or research whose research objects are traced through various library information (books, encyclopedias, scientific journals, newspapers, magazines, and documents). Furthermore, the data collection technique used is a library study. A library study is a data collection technique used to collect data and research sources through books, journals, magazines, newspapers, and so on. The results of this study indicate that parenting styles at home have implications for students' emotional development. Students' emotional development can be fostered through simple measures, such as parents visiting their children less frequently at the Islamic boarding school and giving their children the confidence and courage to meet all their needs at the boarding school. This can make children dependent on their parents and slow the process of developing independence. Furthermore, Islamic boarding schools play a crucial role in fostering independence in their students. This is typically done by assigning responsibility to administrators to assist students, especially new students. In addition to the administrators, the dormitory head also plays a role in guiding the students under his care in developing independence.